Influence of palliative care policy on place of death for people with different cancer types: a nationwide’ register study - Joakim Öhlén; Nyblom Stina; Ozanne Anneli; Nilsson Stefan; Gyllensten Hanna; O’Sullivan Anna; Fürst Carl Johan; Larsdotter Cecilia (PLoS ONE, 2025)
This study investigated the impact of a national palliative care policy introduced in 2013. The hypothesis was that end-of-life and palliative care policy shape healthcare services, which in turn influence service utilisation and ultimately place of death for people dying from cancer. The aim was to identify longitudinal trends in place of death for people with cancer in Sweden. A population-level longitudinal trend in place of death study was performed, based on register data of all adults aged 18 or above with a cancer diagnosis as underlying cause of death in Sweden between 2013-2019. Data were retrieved from registers at the Swedish National Board of Health and Welfare and Statistics Sweden. In addition to a more descriptive overview of place of death (hospital, home, nursing home, and other places), linear regression models were used to analyse trends in place of death and associated socio-demographic factors, and healthcare services and utilisation. Dying in hospital was most common (48.7%), followed by nursing home (25.6%) and own home (23.5%), and differed according to sex, age, marital status, type of cancer, healthcare regions, and utilising specialised palliative care services at death or not. From 2013 to 2019 the total number of home deaths increased from 21.8% to 24.7%, whereas hospital deaths decreased from 49.2% to 47.1%. For people residing in their own home, there was a downward trend for dying in hospital, while no trend was detected for people residing in nursing homes. The identified trend had cross-regional variations and inconsistencies. In conclusion, the hypothesis was not confirmed. The results point to inequity in palliative cancer care, and need for national governance strategies and improved integration of palliative care in national healthcare structures.